Acute lymphoblastic leukemia arising after treatment of Ewing sarcoma was misdiagnosed as bone marrow metastasis of Ewing sarcoma: A case report. Issue 3 (January 2018) - Li, Xiaohong; Li, Wenchao; Mo, Wuning; Yang, Zheng
Abstract: Rationale: Both acute lymphoblastic leukemia (ALL) and Ewing sarcoma (ES) are small round cell tumors, and it is difficult to differential diagnose them because of overlapping clinical, radiographic, histologic, and immunophenotypic features. Patient's concerns: A 5-year-old boy was admitted to our hospital because of pains in his left leg without obvious inducement and lameness worsening with walking over a two 2-month period. Diagnoses: Based on the comprehensive analysis of radiography, magnetic resonance imaging (MRI), pathology biopsy and immunohistochemistry, the lesion was confirmed to be ES. Interventions: The patient received neoadjuvant chemotherapy with 2 cycles of VAC (vincristine 1 mg/m 2, adriamycin 50 mg/m 2, cyclophosphamide 800 mg/m 2 ) and 2 cycles of IE (ifosfamide 1.2 g/m 2, etoposide 70 mg/m 2, mesna 1.2 g/m 2 ) regimens. Outcomes: After 16 months, the results of routine blood tests showed reduced hemoglobin levels and decreased platelet counts. In addition, blast-like cells were found in a peripheral blood smear. All of the results suggested that the patient should undergo bone marrow aspiration and biopsy, which showed blast-like cells similar to that observed in cases of ES. Thus, a diagnosis of bone marrow metastasis of ES was established. However, when combined with immunohistochemistry data and medical history, the patient was eventually diagnosed as ALL arising after treatment of ES. Lessons: When there was an abnormality in peripheral blood, it was easily misdiagnosed as bone marrow metastasis of ES after ES patient received neoadjuvant chemotherapy. We should jointly analyze bone marrow aspiration smear, bone marrow biopsy, immunohistochemistry, analysis of the medical history, even cytogenetic and molecular analysis for differential diagnosis.